P116 Multidrug-resistant tuberculosis (MDR-TB) monitoring in southeast london using current recommendations; does it prevent complications?. (15th November 2016) - Bradley, B; Kamalanathan, M; Shah, AJ; Read, N; Hall, J; Belton, M; Baker, L
Abstract : Background: MDR-TB requires an intense treatment course with multiple drugs, many of which have significant recognised side effects. Frequency of monitoring to prevent long term complications is not fully established, but recent guidelines have gone some way to addressing this. In light of this we wanted to review the side effects of MDR-TB treatment in our population to identify whether our previous practice was in line with the current recommendations and if not, whether the currently recommended frequency could have identified these complications sooner. Methods: 26 patients referred to our trust over 13 years (between 2002 and 2015) had a diagnosis of MDR-TB on a basis of isoniazid and rifampicin resistance on culture and/or PCR. Medical records were reviewed; diagnostic tests, resistance profiles, baseline investigations, treatment, drug monitoring tests and side effects were recorded on 21 of these patients. These were compared with current European Respiratory Society guidelines for MDR-TB management. Results: All baseline tests were completed except for magnesium and electrocardiogram. 6 patients had care transferred elsewhere. Amikacin/cycloserine levels were performed in line with recommendations. Interval blood testing was not always undertaken as recommended, particularly near the end of treatment. 11/15 (73%) of patients experienced at least 1 complication to treatment. Most frequent were: amikacin induced ototoxicity in 5/15 (33%), PAS/prothionamide induced hypothyroidism in 3/15 (20%). Other complications included photosensitivity with pyrazinamide, clofazimine associated erythema, peripheral neuropathy secondary to linezolid/cycloserine, amikacin induced renal impairment and ureteric colic secondary to calculi. Audiometry revealed high frequency hearing loss prior to development of symptoms. One patient developed ototoxicity despite monthly audiometry testing. Hypothyroidism developed despite monthly thyroid function. Conclusions: In our population there was a high incidence of significant side effects to MDR-TB regimes. Ototoxicity with amikacin is a significant concern. While frequent testing is advocated we found that complications were not necessarily negated by this. Frequency of testing was easier to achieve whilst an inpatient than an outpatient. With the advent of the World Health Organisation shorter MDR-TB regimen, the need for regular monitoring remains crucial, but the shorter duration of injectable drugs may also help decrease complication rates in the future.